Human gait recognition with cane assistive device using quadratic time–frequency distributions. Issue 9 (1st December 2015) - Amin, Moeness G.; Ahmad, Fauzia; Zhang, Yimin D.; Boashash, Boualem
Abstract : In this study, the authors consider the problem of human gait recognition in the presence of a walking cane using radars. Quadratic time–frequency distributions are used to provide the local signal behaviour over frequency and to detail the changes in the Doppler and micro‐Doppler signatures over time. New features that capture the intrinsic differences in the time–frequency signatures of the gait observed with and without the use of a cane are proposed. The results based on real data experiments conducted in a laboratory environment are provided that validate the effectiveness of the proposed features in discriminating gait with cane from normal human gait.